2018
DOI: 10.3791/58202
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Low Copy Number Integrated Viral DNA Formed by <em>In Vitro</em> Hepatitis B Infection

Abstract: Hepatitis B Virus (HBV) is a common blood-borne pathogen causing liver cancer and liver cirrhosis resulting from chronic infection. The virus generally replicates through an episomal DNA intermediate; however, integration of HBV DNA fragments into the host genome has been observed, even though this form is not necessary for viral replication. The exact purpose, timing, and mechanism(s) by which HBV DNA integration occurs is not yet clear, but recent data show that it occurs very early after infection. Here, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Here, we used Huh7-NTCP cells, which we have previously shown to be a suitable system for quantifying HBV DNA integration. 32 , 37 We confirmed that comparable levels of cccDNA are formed by WT or ΔHBc HBV in this system ( Fig. S3 ).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Here, we used Huh7-NTCP cells, which we have previously shown to be a suitable system for quantifying HBV DNA integration. 32 , 37 We confirmed that comparable levels of cccDNA are formed by WT or ΔHBc HBV in this system ( Fig. S3 ).…”
Section: Resultssupporting
confidence: 75%
“…Integrated HBV DNA in in vitro infected cells was quantified by inverse nested PCR, as previously described. 31 , 32 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation